Implementasi Norma Living Cost dalam Penganggaran Biaya Perjalanan Dinas Luar Negeri PT PAL Indonesia (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the implementation of the Living Cost Norm in budgeting for foreign official travel costs applied at PT PAL Indonesia. This research uses a qualitative descriptive method that is sourced from primary data obtained through observations, interviews, and review of historical documents on foreign official travel and decrees that are the basis for determining the Living Cost Norm. The results showed that the application of the Living Cost Norm at PT PAL Indonesia had been implemented effectively and was able to provide convenience in the process of preparing the foreign official travel budget. However, it was found that the list of countries in the Living Cost Norm provisions did not cover all destination countries, this situation opened up the possibility of disorientation in the process of budgeting foreign official travel costs whose destination countries were not listed in the Living Cost Norm. It is hoped that this research can provide an in-depth description of the implementation of the policy, as well as solutions and best practices that can be applied by similar industries.